Exogenous application of thiamine on upland rice summited to water deficit (Revista de Ciências Agroveterinárias, 2020)
The occurrence of water deficit during the upland rice production cycle may result in lower vegetative development and yield. In this sense, it is possible to use products with a protective effect, such as vitamin B1. The objective of this work was to assess the effects of exogenous thiamine application, on leaves, during and 30 days after plant emergence, on the biometric and productive characteristics of upland rice submitted to an interval with water deficit. The experiment was designed in randomized blocks with five treatments. The treatments were defined as follows: T1 - control without vitamin application; T2 - application of 50 mg L-1 thiamine in seedling emergence; T3 - application of 50 mg L-1 thiamine 30 days after emergence; T4 - application of 100 mg L-1 thiamine in seedling emergence; T5 - application of 100 mg L-1 thiamine 30 days after emergence. Water stress was applied when the plants were at a stage ranging from V3 to V6. Relative levels of chlorophylls “a,” “b,” and total, plant height, number of tillers, length, and number of panicles per square meter, 1000 grains weight, spikelet fertility, and yield were assessed. Thiamine application was highlighted 30 days after emergence, increasing panicle length, 1000 grains weight, and spikelet fertility by 16.4%, 8.4%, and 6.0%, respectively. The application of thiamine as a foliar treatment mitigates the effects of water deficiency on the biometric and productive characteristics of upland rice plants, mainly when applied 30 days after plant emergence and at a concentration of      100 mg L-1.
Keywords: Oriza sp.; vitamin B1; abiotic stress; plant protection